PENGARUH KEY AUDIT MATTERS DISCLOSURE TERHADAP STOCK MISPRICING (Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Achmad Viki Rainoris; R. R. Sri Handayani (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of Key Audit Matters (KAM) disclosure on stock mispricing. KAM disclosure is proxied by three dimensions: KAM Word, KAM Number, and KAM Readability. This study is grounded in the implementation of ISA 701 audit standards, which are expected to reduce information asymmetry and enhance the communicative value of auditor reports in the capital market. The population comprises consumer cyclicals companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Using purposive sampling, a total of 249 panel data observations were obtained. The results indicate that KAM disclosure, in terms of narrative (Word), quantity (Number), and readability (Readability), has no significant effect on stock mispricing. These findings suggest that investors have not utilized KAM information as a basis for investment decisions affecting stock valuation, presumably because investors focus more on quantitative financial performance indicators than audit risk narratives